2020
DOI: 10.23876/j.krcp.19.082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of online hemodiafiltration on anemia and nutritional status in chronic hemodialysis patients

Abstract: Background: Online hemodiafiltration (OL-HDF) offers considerable advantages in clearance of molecules of various sizes. However, evidence of clinical effects of OL-HDF is scarce in Korea. In this study, we investigated changes in laboratory values over more than 12 months after switching to OL-HDF. Methods: Adult patients with end-stage renal disease undergoing hemodialysis (HD) were prospectively enrolled in a K-cohort (CRIS no. KCT0003281) from 6 tertiary hospitals in South Korea. We recruited 435 patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
10
1
1
Order By: Relevance
“…In this work we didn't find any difference between both groups as regard blood hemoglobin levels. This is against Lee et al (13) , who showed significant improvement in blood hemoglobin level in online HDF group compared to high flux HD, which may be attributed to longer duration (24 months) and larger sample size.…”
Section: Discussioncontrasting
confidence: 70%
“…In this work we didn't find any difference between both groups as regard blood hemoglobin levels. This is against Lee et al (13) , who showed significant improvement in blood hemoglobin level in online HDF group compared to high flux HD, which may be attributed to longer duration (24 months) and larger sample size.…”
Section: Discussioncontrasting
confidence: 70%
“…Post hoc and pooled analyses suggest that a high convection volume may be needed to show better outcomes in online-HDF than in conventional HD 22 , 23 , 25 . European regulatory authorities have allowed online-HDF to be used in patients with uncontrolled hyperphosphatemia and those suffering from complications such as amyloidosis 21 , 42 , but this issue may not be similarly accepted in other countries because of limitations in setting up online-HDF. Before conducting online-HDF, new machines, quality control in substituting fluids, and trained staff are needed, all of which limit its utilization, particularly in primary clinics or developing countries 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Albumin loss via HDF can differ depending on the dialyzer, dialysis modalities, and convection volumes. Previous studies have reported a wide range of albumin loss between 0.5 and 4.5 g per session in postdilution HDF [34][35][36]. The amount of albumin loss in mixed-HDF is not well known.…”
Section: Discussionmentioning
confidence: 99%